Faculty satisfaction with new faculty orientation processes during the first year of employment at the U.S. Army Command and General Staff College: an exploratory study - Persyn, John Michael (Kansas State University, 2008)
This exploratory study investigated the level of satisfaction that faculty members have with their new faculty orientation experiences during their first year of employment at the U.S. Army Command and General Staff College, in Ft. Leavenworth, KS. The study solicited data from new faculty at this graduate-level military service college to help determine whether new faculty members were satisfied with their new faculty orientation experience; whether there were differences in the dependent variable, satisfaction, for any of the independent variables of campus location, teaching department, employment category, academic rank and educational level; and how the CGSC new faculty orientation program might be improved. Surveys were distributed to 297 new faculty members from January 2006 to December 2007. The survey instrument included Likert-scale questions to support quantitative statistical analysis. The study used non-parametric analysis methods to examine the dependent variable, satisfaction, with respect to independent variables. These results indicated that faculty members were satisfied with their new faculty orientation experiences and that there were no significant differences in satisfaction for campus location, teaching department, employment category, academic rank or educational level. Open-ended questions provided respondents an opportunity to add additional information; these comments were categorized by topic and then examined for themes or trends. Despite their overall satisfaction with the orientation program and processes, 84.80% of respondents indicated that inadequate institutional support was the greatest detractor to their success. They cited delays in meeting fundamental new employee needs such as providing a suitable work location, computer access, and information about institutional policies and procedures. Additionally, 35.67% of respondents indicated that either their sponsor was not helpful or none was assigned. Results of this study provided insight regarding unmet or inadequately fulfilled information and support needs of new faculty members at CGSC, informed further research in the area of faculty orientation, and highlighted areas for improvement of practice at CGSC and comparable institutions.
Keywords: Faculty orientation; Faculty development; New faculty; Faculty satisfaction; Education, Adult and Continuing (0516)